Quantitative determination of decitabine incorporation into DNA and its effect on mutation rates in human cancer cells. Issue 19 (26th August 2014) - Öz, Simin; Raddatz, Günter; Rius, Maria; Blagitko-Dorfs, Nadja; Lübbert, Michael; Maercker, Christian; Lyko, Frank
Abstract: Decitabine (5-aza-2′-deoxycytidine) is a DNA methyltransferase inhibitor and an archetypal epigenetic drug for the therapy of myeloid leukemias. The mode of action of decitabine strictly depends on the incorporation of the drug into DNA. However, DNA incorporation and ensuing genotoxic effects of decitabine have not yet been investigated in human cancer cell lines or in models related to the approved indication of the drug. Here we describe a robust assay for the quantitative determination of decitabine incorporation rates into DNA from human cancer cells. Using a panel of human myeloid leukemia cell lines we show appreciable amounts of decitabine incorporation that closely correlated with cellular drug uptake. Decitabine incorporation was also detectable in primary cells from myeloid leukemia patients, indicating that the assay is suitable for biomarker analyses to predict drug responses in patients. Finally, we also used next-generation sequencing to comprehensively analyze the effects of decitabine incorporation on the DNA sequence level. Interestingly, this approach failed to reveal significant changes in the rates of point mutations and genome rearrangements in myeloid leukemia cell lines. These results indicate that standard rates of decitabine incorporation are not genotoxic in myeloid leukemia cells.